Nail apparatus melanoma: epidemiological, clinical and histopathological analysis - Sobjanek, Michał; Michajłowski, Igor; Biernat, Wojciech; Drucis, Kamil; Włodarkiewicz, Adam; Roszkiewicz, Jadwiga (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Nail apparatus melanoma is an uncommon type of cutaneous melanoma with poor prognosis. Tumour accounts for 1% of all cutaneous melanoma in Caucasians. Objective . Investigation on frequency, clinical and histopathological characteristics of nail apparatus melanoma in a Northern Poland population. Material and methods . One thousand five hundred and eighty-eight patients with various nail apparatus pathology who were referred to the Department of Dermatology, Venerology and Allergology, Medical University of Gdańsk, from 2005 to 2010, were included in the study. Among all these patients 8 cases of nail apparatus melanoma were diagnosed. There were 5 women and 3 men (mean age 59 years). Results . Nail apparatus melanoma was observed in 0.504% of patients with nail pathology. All patients were of Fitzpatrick skin type III or IV. Tumours were located in the majority of cases on the great toe and thumb. The most common histopathological variant was acral lentiginous melanoma. The average Breslow thickness was 7.2 mm (range 2.5–18 mm). The 20-month survival rate was 37.5%. Conclusions . Nail apparatus melanoma is rare in the Northern Poland population but it is the most common nail apparatus malignancy. In our population tumours were diagnosed in advanced stages, which is related to poor prognosis.